Answer:
720
Step-by-step explanation:
Answer:
3/2
Sorry for the bad handwriting.
Here is your answer! The coefficient of xy is 6. To solve this problem, you need to multiply your two polynomials together. I used the FOIL Method- multiply the First two, the Outside two, the Inside two, and the Last two. You can see how I did it on the picture attached. Next, the answer that you get as a result from FOILing is your polynomial. If you look at the number before xy, that is the coefficient. A coefficient is a number that is right before and attached to a variable. I hope this helps you! :))
Answer:
Step-by-step explanation:
- x + y + z = -3 --> (1)
- 3y - z = 4 --> (2)
- 2x - y - 2z = -5 --> (3)
<u>Add up (1) and (2)</u>
- x + 3y + y + z - z = -3 + 4 ⇒ x + 4y = 1 --> (4)
<u>Double (2) and subtract from (3)</u>
- 2x - y - 2z - 2(3y - z) = -5 - 2(4) ⇒ 2x - y - 2z - 6y + 2z = -5 - 8
- 2x - 7y = -13 --> (5)
<u>Double (4) and subtract (5)</u>
- 2(x + 4y) - 2x + 7y = 2 + 13 ⇒ 2x + 8y - 2x + 7y = 15 ⇒ 15y = 15 ⇒ y = 1
<u>Finding x</u>
- x + 4(1) = 1 ⇒ x = 1 - 4 ⇒ x = -3
<u>Finding z</u>
<u>So the answer is: </u>